Examining Inhomogeneous Degradation of Graphite/Carbon Black Composite Electrodes in Li-Ion Batteries by Lock-In Thermography. Issue 9 (1st January 2017) - Michalowski, Peter; Gräfenstein, Alexander; Knipper, Martin; Plaggenborg, Thorsten; Schwenzel, Julian; Parisi, Jürgen
Abstract : Understanding the degradation of graphite anodes plays a major role in the improvement of Li-ion batteries. Herein, we used the nondestructive character of lock-in thermography (LIT) to investigate the aging of graphite anodes in pouch cells. The aged cells show a typical ring pattern in lock-in thermography images, which can be explained by the help of Raman spectroscopy. We attribute this pattern to the different contact due to the formation of a gas during operation, which also leads to inhomogeneous degradation of the graphite electrode. Finally, we demonstrate the detection of two-dimensional variances on the sub-mm scale in the composition of the graphite anodes in pouch cells by LIT. For this purpose, we combined LIT measurements with Raman spectroscopy mapping to link differences in the heat emission to those in the structure of the graphite.